Imaging and reporting considerations for suspected physical abuse (non-accidental injury) in infants and young children. Part 1: initial considerations and appendicular skeleton. Issue 3 (March 2017) - Paddock, M.; Sprigg, A.; Offiah, A.C.
Abstract : Recognising the skeletal manifestations of inflicted injury (II) in infants and young children is of crucial importance. There are specific fracture patterns which are highly suspicious of II in addition to common differential diagnoses with which radiologists should be familiar. Our objective is to provide a non-exhaustive review of the important factors relevant to the imaging and reporting of II as a platform for further learning. Part 1 encompasses important initial considerations and fracture patterns of the appendicular skeleton.